PENINGKATAN KUALITAS PELAYANAN PUBLIK PADA ORGANISASI PERANGKAT DAERAH MELALUI PENYEDIA PELAYANAN DASAR DI KABUPATEN BONDOWOSO - Moh. Erfan Arif; Noermijati Noermijati; Yenny Kornitasari; Rizka Fitriasari; Siti Rahmasari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Basic services are the primary needs of the community which must be provided by the government to meet the basic needs of citizens. These basic services can be in the form of health services, education, clean water, economics, electricity, transportation and its support. Quality services provided by the public service organizer unit or the Regional Development Organization (OPD) are a right to be accepted by the community. The purpose of this programme is to know and improve the quality of public service in the basic service providers in Bondowoso Regency. The public service is being evaluated by the Department of Social Affairs, the Regional General Hospital (RSUD) Dr. Koesnadi, the Department of Integrated Capital Services One Door and Labour, the Civil Occupation and Registration Department, the Health Department, and the Department of Education. The method of assessing the quality of public services is carried out using a self-evaluation approach with intense direction and assistance from facilitators and using a 0-5 Likert scale. Indicators for assessing the quality of public services are based on Permenpan RB Number 5 of 2023 concerning Monitoring and Evaluation of the Performance of Public Service Delivery which consists of six aspects and thirty indicators. The results of public service performance by the OPD providing basic services are the Department of Social Service (Excellent Service), the Regional General Hospital (RSUD) dr. Koesnadi (Excellent Service), the Department of Integrated Capital Services One Door and Labour (Good), Population and Civil Registration Service (Good), Health Service (Good with Records), and Education Service (Fair). Overall, the public service performance of several basic public service units falls into the good category (B). This assessment should be carried out regularly at least once a year to maintain the quality of public services so that the public obtains excellent satisfaction.